The cellular triumvirate: fibroblasts entangled in the crosstalk between cancer cells and immune cells - Fergatova, Adel; Affara, Nesrine I. (Frontiers in Immunology, 2024)
This review article will focus on subpopulations of fibroblasts that get reprogrammed by tumor cells into cancer-associated fibroblasts (CAFs). Throughout this article, we will discuss the intricate interactions between fibroblasts, immune cells, and tumor cells. Unravelling complex intercellular crosstalk will pave the way for new insights into cellular mechanisms underlying the reprogramming of the local tumor immune microenvironment and propose novel immunotherapy strategies that might have potential in harnessing and modulating immune system responses.